Beta-blockers are associated with better long-term survival in patients with Takotsubo syndrome. Issue 17 (31st March 2022) - Silverio, Angelo; Parodi, Guido; Scudiero, Fernando; Bossone, Eduardo; Di Maio, Marco; Vriz, Olga; Bellino, Michele; Zito, Concetta; Provenza, Gennaro; Radano, Ilaria; Baldi, Cesare; D'Andrea, Antonello; et al.
Abstract : Objective: The advantage of beta-blockers has been postulated in patients with Takotsubo syndrome (TTS) given the pathophysiological role of catecholamines. We hypothesised that beta-blocker treatment after discharge may improve the long-term clinical outcome in this patient population. Methods: This was an observational, multicentre study including consecutive patients with TTS diagnosis prospectively enrolled in the Takotsubo Italian Network (TIN) register from January 2007 to December 2018. TTS was diagnosed according to the TIN, Heart Failure Association and InterTAK Diagnostic Criteria. The primary study outcome was the occurrence of all-cause death at the longest available follow-up; secondary outcomes were TTS recurrence, cardiac and non-cardiac death. Results: The study population included 825 patients (median age: 72.0 (63.0–78.0) years; 91.9 % female): 488 (59.2%) were discharged on beta-blockers and 337 (40.8%) without beta-blockers. The median follow-up was 24.0 months. The adjusted Cox regression analysis showed a significantly lower risk for all-cause death (adjusted HR: 0.563; 95% CI: 0.356 to 0.889) and non-cardiac death (adjusted HR: 0.525; 95% CI: 0.309 to 0.893) in patients receiving versus those not receiving beta-blockers, but no significant differences in terms of TTS recurrence (adjusted HR: 0.607; 95% CI: 0.311 to 1.187) and cardiac death (adjusted HR: 0.699; 95% CI: 0.284 to 1.722). The positive survival effect of beta-blockers was higher in patients with hypertension than in those without (pinteraction =0.014), and in patients who developed cardiogenic shock during the acute phase than in those who did not (pinteraction =0.047). Conclusions: In this real-world register population, beta-blockers were associated with a significantly higher long-term survival, particularly in patients with hypertension and in those who developed cardiogenic shock during the acute phase.